THE THE EFFECT OF HEART-HEALTHY GYMNASTIC EXERCISE TO CARDIORESPIRATORY ENDURANCE OF OVERWEIGHT FEMALE STUDENTS OF PHYSIOTHERAPY DEPARTMENT, MEDICAL FACULTY, UDAYANA UNIVERSITY - Vittala, Govinda; Nurmawan, I Putu Sutha; Silakarma, Dedi; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 4 No 3 (2016): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Cardiorespiratory endurance is the ability of the heart, blood vessels and lungs that did not experience excessive fatigue in carrying out daily activities. Each additional 1 kg/m2 body mass index will lower the value of cardiorespiratory endurance of 1,349 mlO2/kg/min. This research aimed to identify the effect of heart-healthy gymnastic exercise to cardiorespiratory endurance of overweight female students. This research conducted an experimental research, designed with Pre and Post Test Control Group Design with simple random sampling technique was conducted to obtain the samples. There were 20 people as the samples divided into two groups with each group consisted of 10 persons; treatment group applied to do heart-healthy gymnastic exercise while control group received no treatment. Data-obtaining process was conducted by measuring cardiorespiratory endurance, applying Cooper 12 minute run test before and after the treatment for the two groups. Normality and homogenity data were tested by applying Saphiro-Wilk Test and Levene’s Test. There was a significant change of paired sample t-test result to treatment group by p=0,000 (p<0,05) while control group did not gain significant change in the amount of p=0,799 (p>0,05). Comparative analysis by applying independent t-test showed a significant change between treatment group and control group where p=0,000 (p<0,05). Therefore, it was concluded that heart-healthy gymnastic exercise was effective in improving cardiorespiratory endurance. Keywords: cardiorespiratory endurance, heart-healthy gymnastic, overweight